Examination of Restaurants Online Pricing Strategies: A Game Analytical Approach. Issue 6 (18th August 2017) - Guo, Xiaolong; Zheng, Xiabing
ABSTRACT: This article studies the optimal pricing strategy employed by restaurants in cooperation with third-party websites. Using a mixed game model that consists of a Nash game among multiple restaurants and a Stackelberg game between these restaurants and a third-party website, this paper describes the cooperation and competition among the participants. Results suggest that the restaurants may not always provide price discounts for the third-party website because of the switching behaviors of their offline loyal customers. Moreover, the cooperation between a restaurant and a third-party website is encouraged only when the number of loyal customers is smaller than a threshold, which also depends on restaurant capacity.